EVALUASI pH DAN ALUMINIUM (AL+) DALAM TANAH DI KAMPUNG ERAMBU DISTRIK SOTA KABUPATEN MERAUKE - Parjono Parjono; Yosehi Mekiew; Kayus Wahi (Musamus AE Featuring Journal, 2022)
Soil plays an important role in agriculture, soil cannot be separated from soil fertility in order to obtain maximum results. Soil quality on soil fertility is determined by the interaction of a number of physical, chemical and biological soil properties. pH, c-organic, and Al are some of the quality factors of soil fertility. Evaluation of pH, c-organic, and Al content aims to find out the current conditions and what solutions must be made. The research method was carried out by taking disturbed soil samples on primary, secondary, residential, and grassland lands, then carried out soil laboratory analysis. The results showed that: actual and potential soil pH is highest on residential land. The actual pH is 7.61 and the potential is 6.75 and is classified as neutral. While the actual pH in secondary forest, primary forest, and grasslands, the soil pH ranges from 4.42-4.99 which is classified as acid and the potential pH is 3.81-4.19 and is classified as very acidic. Meanwhile, the Al+ content was relatively low for each land use, namely 1.81-5.76 cmol/kg.